Artificial Intelligence and Transparency Management in the Public Sector: A Comparative Legal Study on Accountability and Oversight in European and American Laws - Al-Shawabkeh, Faisal Abdul-Hafez; Al-Jasmi, Khalid (Journal of Posthumanism, 2025)
This paper looks into how artificial intelligence influences openness in the public sector and examines the laws in Europe and the United States relating to this issue. The European regulations focus on safeguarding individual rights and privacy, while the laws in the United States prioritize creating anti-corruption measures that hold the government accountable. Various artificial intelligence tools, such as large-scale data analysis and blockchain technology, have significant promise for enhancing transparency and supporting efficient detection and decision-making. However, these technological advancements introduce several legal challenges, making it difficult to achieve clarity regarding algorithms and to identify legal responsibilities, which complicates effective judicial oversight. The AI Act of 2024, introduced by the European Union, is among the main EU regulations as it requires transparency standards for high-risk AI systems. The United States employs various sector-specific regulations instead of a single comprehensive framework for oversight. The study concludes that artificial intelligence requires tailored legal frameworks to ensure transparency while maintaining accountability and protecting essential human rights, along with facilitating judicial oversight.